Global financial crises: an exploratory conceptual survey of selected literatures from an Islamic perspective - Abdul Razak, Dzuljastri; Mohammed, Mustafa Omar (2011)
The world has been experiencing increasingly frequent financial crises. Several reasons have been attributed to the causes of these crises. Most of them are claimed to be technical in nature such as the use of financial engineering, absence of sophisticated, reliable an innovative hedging and risk management instruments. Recently, especially after the 2008 global financial crisis , the focus is shifting to ethics.There is increasing awareness that the unethical behaviors of companies and investors are the main culprit to the crises.There is quite a volume of literature that has discussed this ethical subject from both conventional and Islamic perspectives. The present study has focused on the areas of commonality in both types of literature. It has employed content analysis method to identify the causes of financial crises due to unethical behaviors cited in selected literatures under review. These causes are then categorized into concepts and related to one another individually from both perspectives. By this way, the study has demonstrated the need for an objective conceptual approach to studying the two types of literature deriving from their similarities rather than differences. The study has provided suggestions for future research in the concluding section.